Literature Review: Analisis Target Molekuler Dan Pendekatan Kimia Medisinal Dalam Pengembangan Terapi Kanker Servik - Saeful Amin; Aliya Fayyaza Khairun Nisa; Shilvia Siti Nurohmah; Salla Sabillah (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Cervical cancer is one of the most common cancers worldwide and is largely caused by Human Papillomavirus (HPV) infection, particularly types 16 and 18. The development of this cancer is influenced by the E6 and E7 oncoproteins, which disrupt the function of p53 and Rb proteins, as well as the involvement of cellular signaling pathways such as PI3K/AKT/mTOR and EGFR. Limitations of conventional therapies, such as resistance and side effects, drive the need for more targeted and selective therapeutic agents. This study aims to analyze the main molecular targets of cervical cancer and the medicinal chemistry approaches used in its therapeutic development. The method involved a review of 12 open access articles using molecular docking, molecular dynamics, QSAR, and network pharmacology approaches. The findings identified two main target groups: viral targets comprising the HPV E6 and E7 oncoproteins, and cellular targets including the PI3K/AKT/mTOR pathway, EGFR, PARP1, CDK1, and VEGFR. Various medicinal chemistry strategies, from structure-based and ligand-based drug design to multi-target network pharmacology approaches, proved effective in identifying potential inhibitor candidates. Bioactive compounds such as quercetin, gossypol, bixin, and rutin demonstrated stable interactions with these targets. However, further experimental validation is needed to support the development of clinically effective and safe therapies.